Couple Anti-Swing Obstacle Avoidance Control Strategy for Underactuated Overhead Cranes - Shuo Meng; Weikai He; Na Liu; Rui Zhang; Cungen Liu (Actuators)
Overhead cranes are widely used for transportation in factories. They move slowly by manual operation to prevent the payload from swinging sharply or colliding with sudden obstacles. To address these issues and enhance work efficiency, this paper proposes a couple anti-swing obstacle avoidance control method for 5-DOF overhead cranes. Time polynomial fitting is employed for trajectory planning to achieve obstacle avoidance. To achieve anti-swing of the payloads, a coupled variable incorporating both actuated and underactuated states is defined, alongside a boundary for dynamic performance. Finally, MATLAB simulation and hardware experiments are carried out to verify the reliability and compared with some existing control methods.